2021
DOI: 10.3390/jcm10102048
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Periodontitis and Peripheral Arterial Occlusive Disease in a Prospective Population-Based Cross-Sectional Cohort Study

Abstract: Objectives: Peripheral arterial occlusive disease (PAOD) and periodontitis are common chronic diseases, which together affect almost 1 billion people worldwide. There is growing evidence suggesting a relationship between chronic inflammatory conditions such as periodontitis and PAOD. This study aims to determine an association between both entities using high quality research data and multiple phenotypes derived from an epidemiological cohort study. Design: This population-based cross-sectional cohort study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The association between PD and the risk of PAOD has been discussed since 1998. Two recent systematic reviews and a prospective population-based cross-sectional cohort study have investigated this association [ 20 , 21 , 22 ]. Their results indicated that PD could increase the risk of PAOD.…”
Section: Discussionmentioning
confidence: 99%
“…The association between PD and the risk of PAOD has been discussed since 1998. Two recent systematic reviews and a prospective population-based cross-sectional cohort study have investigated this association [ 20 , 21 , 22 ]. Their results indicated that PD could increase the risk of PAOD.…”
Section: Discussionmentioning
confidence: 99%
“…Trenner et al used DRG reimbursement data derived from the German statistical office to determine how practice patterns differed between federal states in Germany [ 9 ]. Closely related to the latter publication, Jacobi et al and Keller et al used data from a large epidemiological cohort study and administrative data to determine the association between periodontitis and diabetes, respectively, and PAD [ 10 , 11 ]. There is an increasing interest in the modifying role of chronic inflammation in cardiovascular disease development while both diabetes and periodontitis may serve as good examples for research projects.…”
mentioning
confidence: 99%